Toxicity Test on the Combination of Caesalpinia sappan and Zingiber officinale in Rattus norvegicus Induced by Complete Freund's Adjuvant - Salma, Nadiah Armadanti, Tukiran; Sutoyo, Suyatno; Sabila, Fauzia Indah (Folia Medica Indonesiana, 2023)
Highlights: 1. This study determined the toxic effects of combining Caesalpinia sappan and Zingiber officinale extracts, as people need to be aware of the potential side effects of these common herbal remedies for the treatment of rheumatoid arthritis. 2. The combination of Caesalpinia sappan and Zingiber officinale extracts is efficacious and non-toxic as an antiarthritis treatment, hence, the ingredients can be upgraded to standardized herbal medicines and phytopharmaceuticals. Abstract Sappanwood (Caesalpinia sappan) and red ginger (Zingiber officinale) are plant species that have been studied for their efficacy in treating inflammation related to rheumatoid arthritis. This study aimed to examine the effects of combining sappanwood and red ginger in order to determine the potential toxicity of the herbal extracts in medicine. The toxicity testing was carried out in vivo using 32 Wistar strain male white rats (Rattus norvegicus) grouped into eight groups of four. The rats were injected with complete Freund's adjuvant to induce a chronic inflammatory effect. The eight groups consisted of the negative control group, the positive control group, the normal group, and five treatment groups. This study was conducted by observing the animals for toxic symptoms and death to determine the safety of the extracts and drugs. The observation results were analyzed using a one-way analysis of variance (p<0.05). The analysis results showed that weight gain and relative organ weight among the groups had no significant differences (p>0.05). Microscopic examination of the organ preparations observed under a light microscope revealed no significant changes or adverse effects in rats treated with the extracts or drugs. In conclusion, a combination of sappanwood and red ginger ethanol extracts administered orally has no toxic effect in rats injected with complete Freund's adjuvant.